Flow properties of caseinomacropeptide aqueous solutions: Effect of particle size distribution, concentration, pH and temperature - Loria, Karina G. (2018)
The purpose of this research was to evaluate the influence of particle size distribution, pH (5.0–9.0), concentration (1–15 g/100 g.) and temperature (5–60 °C) on the steady shear flow properties of caseinomacropeptide (CMP) aqueous solutions. These measurements were carried out by using a controlled stress rheometer. Flow curves were satisfactorily fitted by the Herschel-Bulkley model. CMP solutions exhibited Newtonian flow dependence, particularly at pH values 5.0–6.0. Non-Newtonian shear thinning behaviour was observed at pH 7.0–9.0. The concentration dependence on viscosity showed two different regimes of viscosity increase (dilute and concentrated). The overlap concentration was 8 g/100 g. The temperature dependent behaviour of CMP solutions fitted to the Arrhenius model regardless pH and concentration, and the calculated activation energy was 20 kJ/mol. The flow behaviour of CMP is explained in terms of peptide-peptide and peptide-water interactions. Based on these results, CMP molecules would form spontaneously micelles at pH > 4.5 in ultrapure water.